The reality of the use of educational techniques and laboratory devices in secondary vocational schools in Lattakia Governorate - Sbeira, Fouad; Ali, Saba (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The purpose of this research is to know the reality of the use of educational techniques and laboratory devices in secondary vocational schools in Lattakia Governorate, The research adopted descriptive analytical method through a questionnaire consisting of (50) words distributed on four axes, has been verified the validity and stability through appropriate statistical methods, And then applied to the study sample which consisted of (127) teachers, assistant teachers and vocational teachers in a number of vocational secondary schools in Lattakia Governorate during the second semester of the academic year (2016-2017), The most important findings of the research: -The degree of ownership of the competencies of the use of educational techniques and laboratory devices in vocational schools and the degree of use of these techniques and devices medium. -The degree of obstacles to the use of educational techniques and laboratory devices in vocational schools and the degree of requirements for the development of this use is high. - There were no statistically significant differences in the identification of the reality of the use of educational techniques and lab equipment in secondary vocational schools in Lattakia Governorate according to the variables of the place of study and the job title. - There were statistically significant differences in the possession of competencies in the use of educational techniques and laboratory devices in vocational schools and the use of these techniques and devices according to the variable training courses for those who followed one or more courses. There were no differences regarding the obstacles of using educational techniques and laboratory equipment in vocational schools. The research concluded with a set of proposals aimed at developing the use of educational techniques and laboratory equipment in vocational secondary schools in Lattakia Governorate.